Health-related quality of life after open transhiatal and transthoracic oesophagectomy for cancer. Issue 3 (5th February 2018) - Kauppila, J H; Johar, A; Gossage, J A; Davies, A R; Zylstra, J; Lagergren, J; Lagergren, P
Abstract: Background: Transhiatal and transthoracic oesophagectomy in patients with oesophageal cancer have similar survival rates. Whether these approaches differ in health-related quality of life (HRQoL) is uncertain and was examined in this study. Methods: Patients undergoing transhiatal or transthoracic surgery for lower-third oesophageal or gastro-oesophageal junctional cancer between 2011 and 2015 were selected from an institutional database. HRQoL outcomes were measured at 6 and 12 months after surgery using validated written questionnaires (European Organisation for Research and Treatment of Cancer QLQ-C30 and QLQ-OG25). Linear mixed models provided mean score differences (MSDs) with 95 per cent confidence intervals, adjusted for preoperative HRQoL, age, physical status (ASA fitness grade), tumour location, tumour stage, neoadjuvant therapy, adjuvant therapy and postoperative complications. MSD values of 10 or more were regarded as clinically relevant. Results: Some 146 patients underwent transhiatal (86, 58·9 per cent) or transthoracic (60, 41·1 per cent) oesophagectomy. The HRQoL questionnaires were returned by 111 patients at 6 months and 74 at 12 months. At 6 months, transthoracic oesophagectomy was associated with worse role function (MSD –12, 95 per cent c.i. –23 to 0; P = 0·046). At 12 months, patients in the transthoracic group had more nausea and vomiting (MSD 11, 0 to 22; P = 0·045), dyspnoea (MSD 13, 1 to 25; P = 0·029) and constipation (MSD 20, 7 to 33; P = 0·003) than those in the transhiatal group. Conclusion: Transhiatal oesophagectomy seems to offer better HRQoL than transthoracic oesophagectomy 6 and 12 months after surgery. Abstract : Favours transhiatal